TMS 2016 145th Annual Meeting &Amp; Exhibition 2016
DOI: 10.1007/978-3-319-48254-5_23
|View full text |Cite
|
Sign up to set email alerts
|

Using Powder Cored Tubular Wire Technology to Enhance Electron Beam Freeform Fabricated Structures

Abstract: Electron Beam Freeform Fabrication (EBF 3 ) is an additive manufacturing technique, developed at NASA Langley Research Center, capable of fabricating large scale aerospace parts. Advantages of using EBF 3 as opposed to conventional manufacturing methods include, decreased design-toproduct time, decreased wasted material, and the ability to adapt controls to produce geometrically complex parts with properties comparable to wrought products. However, to fully exploit the potential of the EBF 3 process developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…al. [4] indicated that the use of flux cored wires containing aluminum, iron and boron allows manufacturing Ti-6Al-4V titanium alloys with a more stable and finer microstructure. The rapid prototyping process using a beam allows to produce a Ti-6Al-4V titanium airframe element at lower cost compared to older solution.…”
Section: Introductionmentioning
confidence: 99%
“…al. [4] indicated that the use of flux cored wires containing aluminum, iron and boron allows manufacturing Ti-6Al-4V titanium alloys with a more stable and finer microstructure. The rapid prototyping process using a beam allows to produce a Ti-6Al-4V titanium airframe element at lower cost compared to older solution.…”
Section: Introductionmentioning
confidence: 99%